SMartyComponents : um processo para especificação de arquiteturas de linha de produto de software componentizadas - Bera, Marcio Henrique Gimenes (2015)
Decrease the resources invested in software development is a topic which has been investigated in academy and industry. Effective software reuse techniques have been explored, such as frameworks and components. Component-Based Development (CBD) is an approach that is aimed at developing software by means of a structured set of components, interfaces and well-defined contracts. CBD is supported by well-established process, such as the UML Components, which focuses on identifying candidate systems components. There are other approaches focusing on reuse, such as Software Product Line (SPL), which represents a set of systems with similar characteristics and certain particularities for a given domain. One of the most important artifacts of an SPL is the SPL Architecture (SPLA), as it represents an abstraction of all possible architectures of specific products. Therefore, Variability Management (VM) activities should be well defined so that the SPLA can reflect the characteristics of an SPL. Stereotype-based Management of Variability (SMarty) is a VM approach, and it stands out for allowing representing variability in UML models, including components. Combining SPL and CBD, could allow exploiting the benefits of both approaches aiming at reducing costs and time-to-market, increasing quality in product development and enabling mass customization of such products. Thus, this work presents the proposal of a process based on the combination of the UML Components and SMarty named SMartyComponents, aimed at specifying component-based SLPAs. An evolution of SMarty was needed for exploring the capability of representing variability components, interfaces, operations and ports according to the UML 2.5. Such on evolution experimentally evaluated providing evidence of its effectiveness. SMartyComponents was empirically evalueted by means of a qualitative study, in which Grounded Theory procedures were adopted from the pont of view of experts on CBD and SPL. Obtained results provided evidence of its feasibility serving as a basis for SMartyComponents improvements.